Deliberation Networks: Sequence Generation Beyond One-Pass Decoding - Xia, Yingce; Tian, Fei; Wu, Lijun; Lin, Jianxin; Qin, Tao; Yu, Nenghai; Liu, Tie-Yan (Advances in Neural Information Processing Systems 30, 2017)
The encoder-decoder framework has achieved promising progress for many sequence generation tasks, including machine translation, text summarization, Q&A, dialog system, image captioning, [etc]. Such a framework adopts an one-pass forward process while decoding and generating a sequence, but lacks the deliberation process: A generated sequence is directly used as final output without further polishing. However, deliberation is a common behavior in human's daily life like reading news and writing papers/articles/books. In this work, we introduce the deliberation process into the encoder-decoder framework and propose deliberation networks for sequence generation. A deliberation network has two levels of decoders, where the first-pass decoder generates a raw sequence and the second-pass decoder polishes and refines the raw sentence with deliberation. Since the second-pass deliberation decoder has an overall picture about what the sequence to be generated might be, it has the potential to generate a better sequence by looking into future words in the raw sentence. Experiments on neural machine translation and text summarization demonstrate the effectiveness of the proposed deliberation networks.